Cellular activity of siRNA oligonucleotides containing synthetic isomorphic nucleoside surrogates. Issue 9 (15th December 2014) - Shin, Dongwon; Lönn, Peter; Dowdy, Steven F.; Tor, Yitzhak
Abstract : Singly and multiply modified synthetic siRNA oligonucleotides, containing highly isomorphic surrogate nucleobases, show high interference activity in cell culture. Abstract : Singly and multiply modified synthetic siRNA oligonucleotides, containing isomorphic surrogate nucleobases, show high interference potency in cell culture, suggesting the highly isomorphic RNA alphabet, based on a thieno[3, 4- d ]-pyrimidine core, is tolerated well by the cellular silencing machinery.